2021
DOI: 10.1016/j.stem.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous clonal labeling reveals uniform progenitor potential in the adult exocrine pancreas

Abstract: Summary The tissue dynamics that govern maintenance and regeneration of the pancreas remain largely unknown. In particular, the presence and nature of a cellular hierarchy remains a topic of debate. Previous lineage tracing strategies in the pancreas relied on specific marker genes for clonal labeling, which left other populations untested and failed to account for potential widespread phenotypical plasticity. Here we employed a tracing system that depends on replication-induced clonal marks. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Within that same cluster, Ogn expression was detected, supporting the idea that OGN is involved in cellular contributions to the extracellular matrix. Considering the OGN + population kinetics across experimental conditions, we observed a 2‐fold increase of Ogn ‐expressing fibroblasts after pancreatitis induction, and persisted in the days after pancreatitis (Figure 3C) in which tissue architecture was largely restored 26 . When ordering cells in pseudo‐time, we observed an anticorrelation of Fabp4 and Ogn , of which Ogn is solely expressed at the end of the trajectory (Figure 3D).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Within that same cluster, Ogn expression was detected, supporting the idea that OGN is involved in cellular contributions to the extracellular matrix. Considering the OGN + population kinetics across experimental conditions, we observed a 2‐fold increase of Ogn ‐expressing fibroblasts after pancreatitis induction, and persisted in the days after pancreatitis (Figure 3C) in which tissue architecture was largely restored 26 . When ordering cells in pseudo‐time, we observed an anticorrelation of Fabp4 and Ogn , of which Ogn is solely expressed at the end of the trajectory (Figure 3D).…”
Section: Resultsmentioning
confidence: 89%
“…Methods are described in detail in Lodestijn et al 26 In brief, acute pancreatitis was induced in adult mice (60‐70 days old), which received intraperitoneal injections with cerulein (Sigma‐Aldrich, C9026) in PBS (50 μg/kg) every hour seven times a day for 2 consecutive days. On the days of cerulean treatment, Metamizol (Sigma‐Aldrich, 46232) in PBS (200 mg/kg) was three times orally administered as analgesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Westphalen et al found that pancreatic Dclk1 + cells are the quiescent progenitor cells involved in tissue regeneration and tumorigenesis 35 . Conversely, Lodestijn et al used an unbiased continuous clonal labeling strategy recently and found that all acinar cells have an equal probability to contribute to acinar cell renewal during homeostasis 36 . Thus, at this point, the question whether a subpopulation of pancreatic acinar cells is able to contribute to new acinar cells in the adult pancreas remains unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic tissue isolation was performed as previously 36 with minor modifications. Briefly, pancreas was minced into small pieces, and transferred to 3 mL 0.5 mg/mL Collagenase P (Roche, 11213873001) dissolved in HBSS together with 5 mM glucose.…”
Section: Methodsmentioning
confidence: 99%